Multiple paths towards education privatization in a globalizing world: a cultural political economy review. Issue 6 (2nd November 2017) - Verger, Antoni; Fontdevila, Clara; Zancajo, Adrián
Abstract: Over the last two decades, education privatization has become a widespread phenomenon, affecting most education systems and giving place to a consistent increase in private school enrolment globally. However, far from being a monolithic phenomenon, privatization advances through a variety of context-sensitive policy processes that translate into multiple policy outcomes. This paper aims at understanding why and how education privatization unfolds in a broad variety of settings and, to this purpose, examines the different manifestations of education privatization on the light of Cultural Political Economy (CPE). The conceptual and analytical tools provided by CPE prove to be particularly well suited to explore such a multi-faceted and multi-scalar phenomenon. CPE has helped us to capture the intersect and tension between different drivers (global and local, material and ideational) of education privatization through the evolutionary mechanisms of variation, selection and retention. On the basis of a systematic literature review methodology, encompassing 227 research papers, the article identifies and systematizes six different paths towards education privatization – understood as groups of frequently associated circumstances, mechanisms and courses of action leading to privatization. Conceived as ideal types, these different paths ultimately allow for a richer understanding of education privatization and show that the international diffusion of education privatization norms and discourses is far from producing policy convergence at a global scale.